Self-powered wearable sensing-textiles for real-time detecting environmental atmosphere and body motion based on surface-triboelectric coupling effect. (31st July 2018) - Zhao, Tianming; Li, Junlang; Zeng, Hui; Fu, Yongming; He, Haoxuan; Xing, Lili; Zhang, Yan; Xue, Xinyu
Abstract: Self-powered wearable sensing-textiles for real-time detecting environmental atmosphere and body motion have been presented. The textile is based on highly-stretchable conductive ecoflex fiber modified with multiwall carbon nanotube and polyaniline (PANI) derivatives (acting as one electrode). The surface of the fiber is twined with varnished wire (acting as the other electrode). Upon applied deformation of stretching or bending, the sensing-textile can harvest the mechanical energy and output electric signals through the triboelectrification effect between PANI and varnished wire. After being attached on the human body, the triboelectric output of the sensing-textile can be used to monitor body motion, including finger bending and body stretching. Interestingly, the triboelectric output of the sensing-textile is significantly dependent on the atmosphere, which can actively distinguish different gas species in the environment. The sensitivity, stability and selectivity against ethanol, ammonia, acetone and formaldehyde are high. The response against 400 ppm ethanol vapor at room temperature is up to 54.73%. The current density is 2.1 × 10 −4 A m −2, and the power density is 4.2 × 10 −5 W m −2 . During both the motion detecting and gas sensing processes, no external electricity power is needed. The triboelectric signal can be treated as not only the sensing signal but also the power source for driving the device. The working mechanism is based on surface-triboelectric coupling effect. The present results can promote the development of self-powered wearable electronics.